A short course of antimicrobial therapy for asymptomatic bacteriuria is safe and effective before urologic procedures - Murat Kutlu; Merve Arslan; Yusuf Ozlulerden; Kevser Ozdemir; Selda Sayin-Kutlu; Zafer Aybek (Journal of Infection in Developing Countries)
Introduction: In the presence of asymptomatic bacteriuria (ASB) before the urological procedure, the duration of antimicrobial treatment is controversial. This study aims to evaluate whether a short course of antimicrobial therapy is safe and effective in cases with ASB before urological procedures.